The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1989
DOI: 10.1017/s0305004100078117
|View full text |Cite
|
Sign up to set email alerts
|

Commutativity ofC*-algebras and associativity ofJB*-algebras

Abstract: A n.c.JB*-algebra is associative and commutative if and only if it has no non-zero nilpotent elements. This generalizes the analogous theorem of Kaplansky forC*-algebras. Different characterizations of associativity are given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…If Condition (1) is fulfilled, then X , endowed with the product x • y := {xuy} and the involution x * := {uxu}, becomes a unital JB * -algebra whose unit is precisely u (see [15]), and hence (2) holds by [56,Theorem 26] (see also [36,Theorem 4]). On the other hand, the implication (2) In relation to the above proof, it is worth mentioning that, contrarily to what happens in the case of C * -algebras, the group of all surjective linear isometries on a JB * -triple X need not act transitively on the set of all unitary elements of X [15,Example 5.7].…”
Section: Unitaries In Jb * -Triplesmentioning
confidence: 99%
“…If Condition (1) is fulfilled, then X , endowed with the product x • y := {xuy} and the involution x * := {uxu}, becomes a unital JB * -algebra whose unit is precisely u (see [15]), and hence (2) holds by [56,Theorem 26] (see also [36,Theorem 4]). On the other hand, the implication (2) In relation to the above proof, it is worth mentioning that, contrarily to what happens in the case of C * -algebras, the group of all surjective linear isometries on a JB * -triple X need not act transitively on the set of all unitary elements of X [15,Example 5.7].…”
Section: Unitaries In Jb * -Triplesmentioning
confidence: 99%
“…Rodríguez-Palacios proved in [69,Theorem 26] that if A is a (unital) non-commutative Jordan V -algebra, we have n(A) = 1 if A is associative and commutative, and n(A) = 1 2 otherwise. The same author in collaboration with Iochum and Loupias showed that the same conclusion holds when A is a (non-necessarily commutative) JB * -algebra [51]. The reader can take a look at [34], and [19,Proposition 3.5.44 and comments in §2.1.47 and page 422] for a more recent approach.…”
Section: Introductionmentioning
confidence: 89%
“…The numerical index is well determined in the case of C * -algebras, JB * -algebras, and non-necessarily commutative JB * -algebras. More concretely, a C * -algebra A satisfies that n(A) = 1 if A is commutative and n(A) = 1 2 otherwise [50], and the same conclusion holds when A is replaced by a (unital) non-commutative Jordan V -algebra [69,Theorem 26] or by a non-necessarily commutative JB * -algebra [34,51] (see also [19,Proposition 3.5.44 and comments in §2.1.47 and page 422]). The results in this section show that every commutative JB * -triple has numerical index one (see Lemma 3.1), while for a JBW * -triple M we show that n(M ) = 1 if M is commutative and 1 e ≤ n(M ) ≤ 1 2 otherwise (cf.…”
Section: The Numerical Index Of a Jb * -Triplementioning
confidence: 99%
See 1 more Smart Citation
“…Let A be an alternative C * -algebra with a unit 1. An element u in A is said to be unitary if the equalities Proposition 2.1 [22,Theorem 26] (see also [16,Theorem 4]). Let A be a nonzero, noncommutative JB * -algebra with a unit 1.…”
Section: Corollary 13 Let a Be A Nonzero C * -Algebra Then The Duality Mapping Of π(A) Is Norm-to-norm Upper Semi-continuous At P Amentioning
confidence: 99%